2018
DOI: 10.1002/ldr.2953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rotational prescribed burning and sheep grazing on moorland plant communities: Results from a 60‐year intervention experiment

Abstract: The effect of prescribed burning for conservation management of plant communities is controversial for moorlands growing on peat. These ecosystems provide many services that may be damaged by fire, hence it is important to fully assess its impact on all aspects of ecosystem structure and function experimentally over relatively long time‐scales. This paper describes change in community composition, major plant species, and plant functional types on moorland on peat in upland Britain over 60 years subject to 3 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…There latter suggests are three potential constraints to the colonization by new species, a lack of (1) propagule availability, (2) regeneration niches (sensu Grubb, 1977), and (3) the small size of the experimental plots (Milligan et al, 2016). In terms of new colonists there has been no colonization by tree species in any of these experiments (Milligan et al, 2016), although in another, larger, long-term experiment at this site (Milligan et al, 2018) one small Betula sapling persisted for some time then died, and a few Picea sitchensis seedlings have been detected recently after a period of ca. 60 years grazing-free (R.H. Marrs pers.…”
Section: Discussionmentioning
confidence: 86%
“…There latter suggests are three potential constraints to the colonization by new species, a lack of (1) propagule availability, (2) regeneration niches (sensu Grubb, 1977), and (3) the small size of the experimental plots (Milligan et al, 2016). In terms of new colonists there has been no colonization by tree species in any of these experiments (Milligan et al, 2016), although in another, larger, long-term experiment at this site (Milligan et al, 2018) one small Betula sapling persisted for some time then died, and a few Picea sitchensis seedlings have been detected recently after a period of ca. 60 years grazing-free (R.H. Marrs pers.…”
Section: Discussionmentioning
confidence: 86%
“…The test was unconditioned because rows and column totals varied. The test assumes independence of observations between each published study; this might not be the case for some long-term studies such as those reporting vegetation changes over time at the Moor House experimental plots in northern England (Milligan et al, 2018, Marrs et al, 2019b, Lee et al, 2013) but here we assumed them to be independent because each successive study reported new observations.…”
Section: Potential Sponsorship Biasmentioning
confidence: 99%
“…For Sphagnum growth/abundance specifically, four papers with grouse industry funding links have suggested positive effects but none have suggested any negative effects, in contrast to 6 negatives and 5 no/mixed effects funded by non-grouse shooting organisations. All four of those positive papers (Lee et al, 2013, Marrs et al, 2019b, Milligan et al, 2018, Harris et al, 2011 are from the same research group, whose long-time head is the President of the Heather Trust, a pro-burning, grouse industry group. Three of those four papers reported results from the same experiment undertaken at the Hard Hill burning plots at Moor House, northern England.…”
Section: Potential Sponsorship Biasmentioning
confidence: 99%
“…Another significant failing of B&H's analysis is the lack of statistical independence. For example, Lee et al (2013a), Marrs et al (2019) and Milligan et al (2018) were included as three independent data points during the analysis of bias within grouse moor industry studies. However, all three studies use the same vegetation data from the same experiment, which means they are not independent.…”
mentioning
confidence: 99%
“…the conclusions) rather than on the results presented. For example, Lee et al (2013a), Marrs et al (2019) and Milligan et al (2018) are classified by B&H as finding a positive effect of burning on Sphagnum growth and abundance, but the results sections of these studies indicate that burning had a mixed effect on Sphagnum, with the direction of the effect depending on time since burn (ibid). It seems odd that researchers would quantify the effects of a study based on its conclusions.…”
mentioning
confidence: 99%